Human Herpesvirus 8 (HHV8) Transmission and Related Morbidity in Organ Recipients. Issue 1 (11th October 2012) - Lebbe, C.; Porcher, R.; Marcelin, A. G.; Agbalika, F.; Dussaix, E.; Samuel, D.; Varnous, S.; Euvrard, S.; Bigorie, A.; Creusvaux, H.; Legendre, C.; Frances, C.; et al.
<x xml:space="preserve">Abstract</x> The aims of the study were to assess the risk of HHV8 transmission resulting from organ transplantation, and related morbidity in liver, heart and kidney transplant recipients. Donor and recipient serologies were screened between January 1, 2004 and January 1, 2005 using HHV8 indirect immunofluorescence latent assay (latent IFA) and indirect immunofluorescent lytic assay (lytic IFA). Recipients negative for latent IFA with a donor positive for at least one test were sequentially monitored for HHV8 viremia and underwent serological tests over a period of 2 years. The results showed that among 2354 donors, HHV8 seroprevalence was 9.9% (lytic IFA) and 4.4% (latent IFA). A total of 454 organ recipients (281 renal, 116 liver and 57 heart) were monitored over a 2‐year period. Seroconversion was observed in 12 patients (cumulative incidence 28%) whose donor had positive latent IFA and in 36 patients (cumulative incidence 29%) whose donors were positive only for lytic IFA, without differences across types of transplants. Positive HHV8 viremia was detected in only 4 out of 89 liver transplant recipients during follow‐up and not in recipients of other types of transplant. Two liver transplant recipients and one kidney transplant recipient developed KS. In conclusion, although HHV8 transmission is a frequent event after organ transplantation, HHV8‐related morbidity is rather rare but can be life threatening. Donor screening is advisable for monitoring HHV8 seronegative liver transplant recipients.